Welcome to Westonci.ca, your one-stop destination for finding answers to all your questions. Join our expert community now! Discover the answers you need from a community of experts ready to help you with their knowledge and experience in various fields. Discover detailed answers to your questions from a wide network of experts on our comprehensive Q&A platform.

In the system below, use equation (1) with equation (2) to eliminate x. Then use equation (1) with equation (3) to eliminate x.
x-y-2z=4 (1)
-x+3y-z=8 (2)
-2x-y-4z=-1 (3)
What is the new 2 × 2 system?
a) 2y – 3z = 12 –3y – 8z = 7
b) 2y – 3z = 12 –3y + 8z = 7
c) 2y – 3z = 12 –2y – 6z = 3